Flow dependent ensemble spread in seasonal forecasts of the boreal winter extratropics. (2nd April 2018) - MacLeod, Dave; O'Reilly, Chris; Palmer, Tim; Weisheimer, Antje
Abstract : Flow‐dependent spread (FDS) is a desirable characteristic of probabilistic forecasts; ensemble spread should represent the expected forecast error. However this is difficult to estimate for seasonal hindcasts as they tend to have a relatively small sample size. Here we use a long (110 year) seasonal hindcast dataset to evaluate FDS in forecasts of boreal winter North Atlantic Oscillation (NAO) and Pacific North American pattern (PNA). A good FDS relationship is found for interannual variations in both the NAO and PNA, with mild underdispersion for negative NAO and PNA events and slight overdispersion for positive NAO. Decadal‐scale variability is seen in forecast errors but not in ensemble spread, which shows little variation on this timescale. Links between forecast errors and tropical heating anomalies are also investigated, though no strong links are found. However, a weak link between strong El Niño warming in the East Pacific and reduced PNA error is suggested. Abstract : Flow dependent spread (FDS) of the DJF forecasts for the (a‐c) NAO and (d‐f) PNA.